The Development of Smart Apps Creator-based Interactive Media to Improve Narrative Text Writing Skills - Titin Amelia; Sri Sukasih (Universitas Muhammadiyah Malang, 2025)
Writing skills are among the crucial abilities in education. This study pertained to the students' lack of narrative text-writing skills. The lack of carefull selection of interactive media might impact the quality of learning process This investigation aims to measure the feasibility, practicality, and effectiveness of Smart Apps Creator-based interactive media to enhance the narrative text writing skills of grade-four students. Analysis, design, development, implementation, and evaluation comprising the ADDIE research model were employed. The outcomes of media validation feasibility revealed a 92% % percentage, and the material validation results revealed a proportion of 91%, so both were in the